Development of Quizizz-based Learning Media on Basic Computer and Network Subjects - Trully Yetti Puspita; Ganefri Ganefri (Indonesian Journal Of Educational Research and Review, 2020)
The impact of the Covid-19 virus affects various sectors of life, including the provision of educational services. For the continuity of education and participating in breaking the chain of spread of the covid-19 virus, the implementation of learning is adjusted to social distancing policies. Teaching and learning activities are carried out at each student's home and carried out through bold media (online). In the learning process, the teacher who acts as the Teacher Center uses a method that causes students to pay less attention to the teacher, and sometimes students experience boredom in learning. This study aims to develop Quizizz in basic computer and network subjects as a learning medium and to see the validity, practicality, and effectiveness of Quizizz as a learning medium in Basic Computer and Network subjects. This study uses the Research and Development (R&D) method with ADDIE development procedures which include Analysis, Design, Development, Implementation and Evaluation. The data analysis technique uses descriptive analysis techniques to describe the value of validity. The results of Quizizz-based learning media in this development research are: the validity of Quizizz-based learning media is declared valid with a value category of 0.87, Quizizz learning practical media based on the responses of two teachers with an average score of 89.4 in the very practical category and student responses with an average score of 85.57 in the very practical category. The effectiveness of Quizizz-based learning media is stated to be effective in improving learning outcomes. Based on the research results, it can be denied that Quizizz-based learning media are valid, practical, and effective to be used as learning media in Basic Computer and Network subjects.